The Influence of Kiai Leadership and Pesantren Culture on Quality and Competitiveness as Mediating Variables - Saerozi, Imam; Sukarji, Sukarji (JURNAL AL-TANZIM, 2024)
This research aims to identify and analyze the influence of Kiai leadership and Pesantren culture on quality and competitiveness as mediating variables. The quantitative research method employs an explanatory research approach with a survey method. The questionnaire was designed based on the research variables, which include leadership, motivation, organizational culture, employee work discipline, and organizational commitment. Data was collected from 97 employees through random sampling. The data analysis utilized multiple regression analysis and the Sobel test. The results indicate that Kiai leadership significantly influences quality, meaning that the higher the Kiai leadership, the higher the quality; Pesantren culture significantly influences quality; Kiai leadership significantly influences competitiveness; Pesantren culture significantly influences competitiveness; competitiveness significantly influences quality, meaning that the higher the competitiveness, the higher the quality. Competitiveness can mediate the relationship between Kiai leadership and quality, indicating that an increase in competitiveness impacts the enhancement of Kiai leadership, thereby improving quality; and also acts as a mediating variable between Pesantren culture and quality, indicating that an increase in competitiveness enhances Pesantren culture, which in turn improves quality.